Predicting the onset of knee pain: results from a 2-year prospective study of new workers. (25th August 2006) - Jones, Gareth T; Harkness, Elaine F; Nahit, Elizabeth S; McBeth, John; Silman, Alan J; Macfarlane, Gary J
Abstract : Objective: To determine the relative contribution of work-related mechanical (injury) factors and psychosocial factors to the onset of a new episode of knee pain, in a cohort of newly employed workers. Methods: A prospective cohort study of newly employed workers from 12 diverse occupational settings in England (The New Workers Study). 859 newly employed workers, free of knee pain, were identified. Information about occupational mechanical factors (manual handling and postural activities), the occupational physical environment, and psychological and psychosocial factors was collected by self-completion questionnaires. Participants were followed up after 12 and 24 months to identify cases of knee pain onset. Generalised estimating equations were used to estimate the risk of new-onset knee pain, with respect to the exposures previously measured. Results: In total, over the 2-year follow-up period, 108 cases of new-onset knee pain were observed. Mechanical load, postural factors, psychological distress and work-place psychosocial factors all influenced the risk of new-onset knee pain over the 2-year follow-up period. On multivariate analysis, two factors remained independently predictive of knee pain onset: lifting or carrying heavy weights in one hand, and the level of general psychological distress. Conclusion: In addition to mechanical (injury) factors, psychological factors are important risk factors for knee pain onset as shown in a population of young newly employed workers.